The Analysis on the Interfaith Marriage Problems Based on the Perspectives of Islamic Law and Human Rights in Indonesia - Rizal, Sofian Syaiful; Sudirman, Sudirman; Toriquddin, Moh (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 3 (2023): The 6th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2023)
Interfaith marriages are relatively widespread and one issue that has sparked controversy in Indonesia. Islamic Law and Human Rights (HAM) has taken a position on legalizing interfaith marriages in Indonesia. This study aims to provide an overview of Indonesian interfaith marriages. The legal interpretation of Islam and human rights concerning the practice of interreligious marriage in Indonesia is described in this research, which is qualitative research. The key data sources for this research, which is also a sort of library research, are legal materials pertaining to interfaith weddings in Indonesia, documents outlining Indonesian Islamic law's interfaith marriage regulations, and documents on human rights. Secondary data sources, additional research findings, and other pertinent papers are also used to support this study. Techniques for gathering data via documents. The study's findings show that the legal perspective encompasses Marriage Law, Islamic religious law, and human rights (HAM), all of which tend to forbid interfaith marriages from taking place. The legality of an interreligious union and the status of any children it produces may be affected.